(untitled) (London Journal of Engineering Research, 2023)
The purpose of this research is to outline a novel methodology for using microstructures to inform Thermal Protection Systems (TPS) materials research. This method involves the Micro- Computed Tomography (Micro-CT) scanning of materials, rendering, segmentation of each element class, and then quantitative analysis of the materials using their microstructures. The microstructures of TPS materials were characterized using the Lawrence Berkeley National Laboratory (LBNL)’s Beamline 8.3.2 at the Advanced Light Source (ALS). The Synchrotron-based Hard X-ray Micro- Tomography instrument allowed for non- destructive 3-Dimensional imaging of 72 different samples of TPS materials. Understanding the behavior and composition of TPS materials before and after aerothermal testing is key to meeting the demands of new space exploration goals so materials were examined in both virgin and char states. Char materials were tested on an Oxy-Acetylene Test Bed (OTB). The Micro-CT scans were then rendered into 3D images, which were manipulated and examined for qualitative learnings about the materials. Deep learning segmentation was then used to separate and label each element within the samples. Finally, segmented samples were used to calculate various material parameters such as weight percent, volume percent, and thermal conduc- tivity. These computed values are then compared to empirical information in order to validate this novel methodology. The applications of this methodology for improving the development and iteration of novel ablative materials will be discussed